ANALISIS KEBUTUHAN PELATIHAN KETERAMPILAN ABACUS ARITMATIKA BAGI GURU MADRASAH - Elice, Deti; Pahrudin, Agus; Syafril, Syafrimen; Koderi, Koderi; Patimah, Siti (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2023)
This research aims to analyze the training needs for arithmetic abacus skills, particularly among teachers at Madrasah Ibtidaiyah Bandar Lampung. The focus is on minimizing errors and failures in achieving expected goals, as well as addressing training outcomes that do not align with the participants' objectives and needs. Through the analysis of training needs for arithmetic abacus skills, the research seeks to identify effective and efficient strategies, methods, materials, and techniques for conducting training that meets the specific needs of teachers at Madrasah Ibtidaiyah Bandar Lampung. The study adopts a qualitative approach with a case study method, selecting research subjects purposively. Data collection involves interviews, observations, and documentation, with the results analyzed descriptively qualitatively.Â The findings of this research emphasize the crucial importance of analyzing the training needs for arithmetic abacus skills in implementing training programs. Prior to conducting training for arithmetic abacus skills, it is essential to gain a comprehensive understanding of participants' initial skills, the methods typically used in their previous training experiences, participants' interests and responses to the upcoming training, as well as any challenges they face in arithmetic abacus skills. This ensures that the training outcomes align with the goals of the training program and meet the specific needs of Madrasah teachers, particularly at Madrasah Ibtidaiyah Bandar Lampung